PENGARUH LATIHAN DROP PASS AND SHOOTING DRILLS TERHADAP KETEPATAN SHOOTING DAN PASSING PEMAIN SEPAK BOLA PUTRA U-15 DI KLUB MAESTRO FC LOMBOK TIMUR TAHUN 2022 - Nova Dwi Kurnia, Subakti, Supriadin, dan Herman Syah (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
Problem Statement: Shooting skills are very important for players because it is impossible to score without it. Meanwhile, mastery of correct passing techniques and the application of efficient techniques can facilitate the passage of the ball between sides in order to achieve the goal (goal). Research objective: This study aims to determine the effect of drop pass and shooting drills on the accuracy of shooting and passing of U-15 male football players at the Maestro FC Club Lombok Timur in 2022. Research Design: The research design used in this study was "one group pretest-posttest design". Population and Sample: The population in this study were all U-15 male football players at the Maestro FC Club Lombok Timur, totaling 24 people. Meanwhile, the sampling technique used in this study was purposive sampling, so that 15 children met the age criteria under 15 years. Research Instruments: The instrument used in this study was a test of shooting skills and passing/stopping skills from Nurhasan (2001). Data Analysis: The data analysis technique used t-test by comparing the mean value of the pretest-posttest results before and after treatment with the same sample. Prior to the t-test analysis, pre-requisites of analysis were conducted in the form of normality and homogeneity tests to determine the results of the data being normally distributed and homogeneous. Results and Discussion: Based on the results of testing the t-test value of shooting accuracy, with a t-count > t-table which is 4,136 > 2,145 at a significant level of 5%, it can be concluded that "there is an effect of drop pass and shooting drills on the accuracy of shooting of U-15 male football players at the Maestro FC Club Lombok Timur in 2022". Furthermore, based on the results of testing the t-test value of passing accuracy, with a t-count > t-table which is 5,801 > 2,145 at a significant level of 5%, it can be concluded that "there is an effect of drop pass and shooting drills on the accuracy of passing of U-15 male football players at the Maestro FC Club Lombok Timur in 2022".